2021
DOI: 10.1111/hiv.13121
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact on direct healthcare costs of missing opportunities for diagnosing HIV within healthcare settings

Abstract: Background The economic consequences of a missed opportunity for HIV testing at an earlier stage of infection within a healthcare setting are poorly described. Methods For all newly diagnosed HIV patients followed at the Southern Alberta HIV/AIDS Clinic (SAC), Calgary, Canada, between 1 April 2011 and 1 April 2016, all clinical encounters occurring < 3 years prior to diagnosis within the region were obtained. The direct costs of HIV care after diagnosis to 31 March 2019 were determined from a payers’ perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Our findings of increased healthcare costs in PLWH compared with their comparisons before HIV diagnosis and most pronounced in the last year before HIV diagnosis could suggest that in some cases the HIV infection could have been diagnosed earlier. This corroborates findings by Gill and colleagues who found that for all newly diagnosed HIV patients between April 2011 and April 2016 at the Southern Alberta HIV/AIDS Clinic, the median number of clinical encounters in the 3 years prior to HIV diagnosis was three [27]. In the Canadian study, 25% of these clinical encounters were for HIV clinical indicator conditions, that is, conditions that are more common in undiagnosed patients with HIV than in the general population and that may be indicative of an underlying HIV diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings of increased healthcare costs in PLWH compared with their comparisons before HIV diagnosis and most pronounced in the last year before HIV diagnosis could suggest that in some cases the HIV infection could have been diagnosed earlier. This corroborates findings by Gill and colleagues who found that for all newly diagnosed HIV patients between April 2011 and April 2016 at the Southern Alberta HIV/AIDS Clinic, the median number of clinical encounters in the 3 years prior to HIV diagnosis was three [27]. In the Canadian study, 25% of these clinical encounters were for HIV clinical indicator conditions, that is, conditions that are more common in undiagnosed patients with HIV than in the general population and that may be indicative of an underlying HIV diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Many high HIV burden countries are striving to reach the UNAIDS target of 95% of PLHIV knowing their status ( 4 ); however, as countries approach this target, the more difficult and more labor-intensive it becomes to find the remaining, often hard-to-reach individuals ( 47 ). Because countries spend millions of dollars each year on HIV case-finding ( 48 ), misinterpretation of any such cases is an expensive failure ( 49 , 50 ). Human error in interpreting positive HIV test results—particularly ones with weak positive lines—is a known and well-documented issue, and many of the proposed interventions to mitigate this issue (e.g., more specialized training for healthcare providers, use of a second test reader) require additional human resources ( 13 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IC-guided HIV testing is an effective approach to identifying undiagnosed HIV-positive individuals [13,14,18,20,36], including saving resources, given that another study revealed that patient costs for those newly diagnosed with HIV were 10 times higher for patients with HIV who had had a previous encounter with the health system related to the diagnosis of an IC than for those with no encounters [37]. However, this strategy is insufficiently implemented in Western countries [21].…”
Section: Discussionmentioning
confidence: 99%